AN ANALYSIS OF IMPLEMENTATION CHALLENGES FOR ENGLISH FOR SPECIFIC PURPOSES (ESP) FORMATIVE ASSESSMENT VIA BLENDED LEARNING MODE AT CHINESE VOCATIONAL POLYTECHNICS - Qiao, Liping; Xu, Yiping; Ahmad, Norkhairi bin (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
In the midst of the current digital learning era, traditional assessment has gradually shifted over prioritizing summative assessment towards equally emphasizing formative assessment within blended learning mode. However, there are still limited studies that investigate the implementation of formative assessment via blended learning mode in China particularly looking at the situation at Chinese vocational polytechnics. To explore actual formative assessment practices, a qualitative case study was conducted at two vocational polytechnics and experienced ESP teachers were selected as participants. Rich data were collected through rounds of semi-structured interviews and document analysis and emerging themes from the elicited and analysed data show five categories of challenges. The findings revealed that though most ESP teachers perceived formative assessment as an effective and fair way to monitor students’ learning process, there are still challenges that must be mitigated especially when implemented via online platforms. The challenges come in the form of difficulty in following ESP assessment principles, limited training and absence of guidelines, large class size, and students’ lack of motivation influence their assessment practices. This study justifies the need to develop explicit guidelines for best practices in ESP formative assessment for teachers’ reference.